Optimalisasi Penerapan Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) dalam Meningkatkan Akuntabilitas Kinerja: Studi Kasus Pada BPBD Kota Magelang - Zulfa, Syaniyatus; Anastasya, Amelia Putri; Sari, Septya Nurmala; Putri, Destiana; Aulia, Harlin (UIR Press, 2025)
The Government Agency Performance Accountability System (SAKIP) is a performance management system designed to promote accountability, transparency, and results-oriented governance in the public sector. However, in practice, the implementation of SAKIP at the local government level often remains administrative and has not been fully optimized as a strategic management tool. This study aims to analyze the implementation of SAKIP and identify optimization efforts to enhance performance accountability at the Regional Disaster Management Agency (BPBD) of Magelang City. This research employs a qualitative descriptive approach with a case study design. Data were collected through observations, semi-structured interviews with key informants, and analysis of performance documents, including the Strategic Plan, Key Performance Indicators, Performance Agreements, and the Government Institution Performance Report. Data analysis was conducted using the interactive model of Miles and Huberman, and data validity was ensured through source and document triangulation. The findings indicate that BPBD Magelang City has implemented SAKIP in accordance with existing regulations; however, its implementation remains largely administrative. Performance indicators are still more output-oriented, and the utilization of performance evaluation results has not been optimal. Therefore, optimizing SAKIP requires strengthening outcome-based indicators, enhancing human resource capacity, and reinforcing a performance evaluation culture.